Pergantian Kepemimpinan Partai Kebangkitan Bangsa Kabupaten Bandung dan Kemenangan Pemilu Legislatif Kabupaten Bandung Tahun 2024 - Suryana, Nanang; Nurzaman, Tedy; Silas, Jonah (HK-Publishing, 2025)
Abstract Party leadership is an important aspect in showing the face of a political party to the public as voters. Several studies show that party leadership has a fairly strong influence in determining voting behavior (Liddle & Mujani, 2007). In the midst of the decentralization system in force in Indonesia, the presence of political parties at the regional level is thus a necessity, at least to reach voters at a more micro level. The touch between the community and the party at the regional level is certainly more intense compared to the party at the central level. The last four legislative elections in Bandung Regency (2004, 2009, 2014, and 2019), were always won by the Golkar party, until finally this dominance collapsed marked by the victory of the National Awakening Party (PKB) in the 2024 Bandung Regency legislative election. This victory occurred after the change in leadership of the National Awakening Party (PKB) at the regional level, in this case in Bandung Regency. Through the conceptual framework built by Stark (1996), related to the criteria for changing party leadership, this article aims to analyze in more depth how the change in leadership of the National Awakening Party of Bandung Regency can provide electoral incentives for the National Awakening Party's vote acquisition in the 2024 Bandung Regency legislative election. This article shows the factors of acceptance of party leaders by party members, electoral interest possessed by party leaders, and the competence of party leaders, which are supported by the factor of ownership of popular power as determinant factors that must be possessed by party leaders, as happened in the National Awakening Party (PKB) of Bandung Regency which succeeded in breaking the dominance of the Golkar Party in the 2024 Bandung Regency legislative election. Keywords: Change of Party Leadership, Popular Political Actors, PKB Abstrak Kepemimpinan partai menjadi aspek penting dalam menunjukkan wajah partai politik kepada publik sebagai pemilih. Beberapa studi menujukan kepemimpinan partai memiliki pengaruh cukup kuat dalam menentukan perilaku memilih (Liddle & Mujani, 2007). Di tengah sistem desentralisasi yang berlaku di Indonesia, kehadiran partai politik pada tingkatan daerah dengan begitu, menjadi suatu keharusan, paling tidak untuk menjangkau pemilih pada tingkatan yang lebih mikro. Sentuhan antara masyarakat dengan partai pada tingkatan daerah tentunya menjadi lebih intens dibandingkan dengan partai pada tingkatan pusat. Empat pemilu legislatif Kabupaten Bandung terakhir (2004, 2009, 2014, dan 2019), selalu dimenangkan oleh partai golongan karya (Golkar), sampai akhirnya dominasi tersebut runtuh ditandai dengan kemenangan partai kebangkitan bangsa (PKB) pada pemilu legislatif Kabupaten Bandung tahun 2024. Kemenangan tersebut terjadi pasca pergantian kepemimpinan partai kebangkitan bangsa (PKB) di tingkatan daerah, dalam hal ini di Kabupaten Bandung. Melalui kerangka konseptual yang dibangun oleh Stark (1996), terkait kriteria pergantian kepemimpinan partai, artikel ini bertujuan untuk menganalisis lebih dalam bagaimana pergantian kepemimpinan partai kebangkitan bangsa Kabupaten Bandung dapat memberikan insentif elektoral terhadap raihan suara partai kebangkitan bangsa pada pemilu legislatif Kabupaten Bandung tahun 2024. Artikel ini menunjukkan faktor penerimaan pemimpin partai oleh anggota partai, ketertarikan elektoral yang dimiliki pemimpin partai, dan kompetensi pemimpin partai, yang ditopang oleh faktor kepemilikan kekuatan popular menjadi faktor determinan yang harus dimiliki oleh pemimpin partai, sebagaimana yang terjadi pada partai kebangkitan bangsa (PKB) Kabupaten Bandung yang berhasil mematahkan dominasi partai golkar pada pemilu legislatif Kabupaten Bandung tahun 2024. Kata Kunci: Pergantian Kepemimpinan Partai, Aktor Politik Popular, PKB